PENERAPAN KONSEP DIDAKTIK DALAM TIM SEPAKBOLA PRO DUTA FC - Fiator Ambarita, - (2021)
This research is motivated by the lack of students' playing skills which makes children less able to interact effectively with peers and their club. This study aims to determine and test the influence of the Implementation Didactics use Cooperative Learning Model on playing skills in football/soccer games. The method used in this study is the CAR method. The population in this study are PRO DUTA FC players. The sample in this study was 15 players. In sampling the researchers used a purposive sampling technique. This study uses an instrument in the form of the GPAI Game Performance Assessment Instrument. The results showed that: The Cooperative Learning Model has a significant influence on playing skills in football/soccer games.